Pengaruh pemberian penyuluhan DAGUSIBU obat terhadap pengetahuan masyarakat di Desa Ketindan - Muthmainnah, Aisya Kayla (Maliki Interdisciplinary Journal, 2023)
Ketindan Village is a village in East Java Province’s Lawang District, Malang Regency. One of the factors in the distribution of urgently required health counseling is access to residents’ homes, which are quite far from the health center. This issue results in a lack of public education about health, treatment, and drug use. Therefore, it is essential to educate the general public through DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) counseling, especially regarding the proper use of drugs. This research is a type of pre-experimental research with a one-group pretest-posttest design. Student pharmacy, UIN Maulana Malik Ibrahim Malang, provided this counseling. The assessment of the evaluation of this counseling activity was based on the pretest and posttest scores of the respondents. The average participant pretest score was 66%, and the posttest score was 86.25%. Based on the pretest and posttest results, it was indicated that the participants’ knowledge before and after being given counseling had increased. The conclusion from this research is that respondents have less knowledge about DAGUSIBU. So that DAGUSIBU counseling is very appropriate so that respondents are able to apply DAGUSIBU in their daily lives to maximize the effect of drug therapy, eliminate drug abuse, and not pollute the environment due to inappropriate drug disposal.